Behaviour-based functional and dysfunctional strategies of medical students to cope with burnout. Issue 1 (1st January 2018) - Erschens, Rebecca; Loda, Teresa; Herrmann-Werner, Anne; Keifenheim, Katharina Eva; Stuber, Felicitas; Nikendei, Christoph; Zipfel, Stephan; Junne, Florian
ABSTRACT: Background : High levels of burnout rates amongst medical students have been confirmed by numerous studies from diverse contexts. This study aims to explore the functional and dysfunctional coping strategies of medical students with regard to their respective burnout factors. Methods : About 845 medical students in the 3 rd, 6 th, and 9 th semesters and students in their final year were invited to take part in the survey. The self-administered questionnaire included items on potential functional and dysfunctional behavioural-based coping strategies as well as the Maslach Burnout Inventory-Student Version (MBI-SS). In addition, a comparison of the local results with a German reference sample involving other students was calculated. Results : A total of 597 medical students (70.7%) participated in the cross-sectional study. The results showed high burnout rates, averaging 35%. Students in earlier stages of university education showed lower values for cynicism (a subdimension of burnout), but higher values for emotional exhaustion than students in higher stages. Concerning academic efficacy, there was a trend towards less efficient perception among students in higher education. The identified functional coping strategies were ' seeking support from friends ', ' seeking support from family ', ' doing relaxing exercise ', ' doing sports ' and ' seeking support from fellow students '. The identified dysfunctional coping strategies were ' taking tranquilizers ', ' taking stimulants ', ' drinking alcohol ', ' withdrawal and ruminating ', and ' playing games on the PC or mobile phone '. The medical students surveyed are more affected by burnout symptoms like emotional exhaustion than the reference populations, but the overall result was difficult to interpret. Conclusions : The identified behavioural-based functional coping strategies suggest that social support and active relaxing exercises seem to be very important possibilities for medical students to reduce stress and exhaustion. The use of drugs and alcohol for stress reduction raises concerns. Programs are recommended to improve resilient behaviour and to impart the identified functional coping strategies to medical students.